Marcel Destombes (1905-1983): Contributions sélectionnées a l'histoire de la cartographie et des instruments scientifiques / Selected Contributions to the History of Cartography and Scientific Instruments - Destombes, M. (HES Studies in the History of Cartography and Scientific Instruments, 1987)
Edited by G. Schilder, P. van der Krogt and S. de Clercq. Includes bibliography of Marcel Destombes (pp. xviii-xxiv).